The role of beta-2-glycoprotein I in health and disease associating structure with function: More than just APS. (January 2020) - McDonnell, Thomas; Wincup, Chris; Buchholz, Ina; Pericleous, Charis; Giles, Ian; Ripoll, Vera; Cohen, Hannah; Delcea, Mihaela; Rahman, Anisur
Abstract: Beta-2-Glycoprotein I (β2GPI) plays a number of essential roles throughout the body. β2GPI, C-reactive protein and thrombomodulin are the only three proteins that possess the dual capability to up and down regulate the complement and coagulation systems depending upon external stimulus. Clinically, β2GPI is the primary antigen in the autoimmune condition antiphospholipid syndrome (APS), which is typically characterised by pregnancy morbidity and vascular thrombosis. This protein is also capable of adopting at least two distinct structural forms, but it has been argued that several other intermediate forms may exist. Thus, β2GPI is a unique protein with a key role in haemostasis, homeostasis and immunity. In this review, we examine the genetics, structure and function of β2GPI in the body and how these factors may influence its contribution to disease pathogenesis. We also consider the clinical implications of β2GPI in the diagnosis of APS and as a potentially novel therapeutic target.